2013
DOI: 10.1037/a0027761
|View full text |Cite
|
Sign up to set email alerts
|

If it makes you happy: Engaging in kind acts increases positive affect in socially anxious individuals.

Abstract: Social anxiety is associated with low positive affect (PA), a factor that can significantly affect psychological well-being and adaptive functioning. Despite suggestions that individuals with high levels of social anxiety would benefit from PA enhancement, the feasibility of doing so remains an unanswered question. Accordingly, in the current study, individuals with high levels of social anxiety (N = 142) were randomly assigned to conditions designed to enhance PA (Kind Acts), reduce negative affect (NA; Behav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
99
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(109 citation statements)
references
References 72 publications
6
99
2
2
Order By: Relevance
“…For example, kindness toward oneself and others has been shown to increase positive affect and enhance resources for life satisfaction (Fredrickson et al, 2008). Engaging in kind acts toward others has been shown to increase positive affect and improve relationship satisfaction in socially anxious people (Alden & Trew, 2013). The present findings suggest that positive affect and kind behavior toward others may be potential mediators in the relationship between self-compassion and life satisfaction, but further study is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…For example, kindness toward oneself and others has been shown to increase positive affect and enhance resources for life satisfaction (Fredrickson et al, 2008). Engaging in kind acts toward others has been shown to increase positive affect and improve relationship satisfaction in socially anxious people (Alden & Trew, 2013). The present findings suggest that positive affect and kind behavior toward others may be potential mediators in the relationship between self-compassion and life satisfaction, but further study is necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in these physiological markers can directly impact health. For example, when we engage in small acts of honesty or virtue, our positive emotions surge [17] which can serve to down-regulate disorders of hyperarousal such as anxiety [18]. Such acts can also lead directly to health benefits such as lower blood pressure and increased longevity [19,20,21 ,22 ].…”
Section: (Dis)honesty In the Bodymentioning
confidence: 99%
“…Layous et al (2012) showed that performing acts of kindness towards others led to increased wellbeing and also increased quality of peer relationships, while Weinstein and Ryan (2010) showed that when people volitionally help others, they experience enhanced wellbeing. Alden and Trew (2013) showed that these effects held even for socially anxious people, such that Positive Affect was increased in people with social anxiety when they undertook kind acts towards other people.…”
Section: Gifting As a Naturalistic Source Of Positive Affectmentioning
confidence: 99%